2013
DOI: 10.1590/s0100-29452013000300027
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da adubação com nitrogênio, fósforo e potássio no desenvolvimento, na produção e na qualidade de frutos do abacaxi 'Vitória'

Abstract: RESUMO-A cultivar de abacaxi 'Vitória' tem como principais características a resistência à fusariose, ausência de espinhos nas folhas, frutos de forma cilíndrica e de polpa branca. O objetivo deste trabalho foi avaliar o efeito de doses de N, P 2 O 5 e K 2 O no desenvolvimento da folha "D", massa dos frutos, produtividade, produção de mudas e qualidade da polpa do fruto -sólidos solúveis (SS) e acidez titulável (AT). Os tratamentos foram constituídos de cinco níveis de N: 0; 214; 428; 642 e 856 kg ha -1 ; cinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 8 publications
2
14
1
12
Order By: Relevance
“…Vitória increased in titratable acidity (0.38%) and soluble solids (17.62%) linearly. However, the application of N had opposite effect (Caetano et al, 2013). The activity of citratesintase and aconitase promotes changes in the acidity of the pineapple.…”
Section: /8mentioning
confidence: 97%
“…Vitória increased in titratable acidity (0.38%) and soluble solids (17.62%) linearly. However, the application of N had opposite effect (Caetano et al, 2013). The activity of citratesintase and aconitase promotes changes in the acidity of the pineapple.…”
Section: /8mentioning
confidence: 97%
“…Vitória, when the fresh mass of leaf D is equal or greater than 70 g or diameter of the minimum stem of 8.5 cm, with a fruit mass equal or greater than 1.2 kg plant -1 . Some authors such as Silva et al (2012); Caetano et al (2013) and Rodrigues et al (2013) reported an effect on the dry and fresh mass of leaf D, using fertilizations with N and/ or K. Oliveira et al (2015b), under dry conditions, verified maximum leaf mass D in 'Imperial' pineapple of 56 g, obtaining fruits of 1,086 g, with the application of 364 kg ha -1 of N and 600 kg ha -1 of K 2 O, and recommended a minimum mass of 44 g of leaf D for the accomplishment of floral induction in 'Imperial' pineapple to obtain fruits with mass greater or equal to 900 g, and to obtain average (1,200 g) and large fruits (1,800 g), it is necessary to have fresh sheet D mass of 62 and 99 g, respectively. Guarçoni & Ventura (2011) verified in cv.…”
Section: Resultsmentioning
confidence: 99%
“…This is an important trait for farmers because they use these slips for future plantings, the slips protect the fruits from sunburn [18] and they can be sold, which ensures an extra source of income [19].…”
Section: Resultsmentioning
confidence: 99%